Writing and Reading Histone H3 Lysine 9 Methylation in Arabidopsis - Xu, Linhao; Jiang, Hua (Frontiers in Plant Science, 2020)
In eukaryotes, histone H3 lysine 9 methylation (H3K9me) mediates the silencing of invasive and repetitive sequences by preventing the expression of aberrant gene products and the activation of transposition. In Arabidopsis, while it is well-known that dimethylation of histone H3 at lysine 9 (H3K9me2) is maintained through a feedback loop between H3K9me2 and DNA methylation, the details of the H3K9me2-dependent silencing pathway have not been fully elucidated. Recently, the regulation and the function of H3K9 methylation have been extensively characterized. In this review, we summarize work from the recent studies regarding the regulation of H3K9me2, emphasizing the process of deposition and reading and the biological significance of H3K9me2 in Arabidopsis.